International business law and its environment - Schaffer, Richard; Earle, Beverley; Agusti, Filiberto (Australia : West / Thomson Learning, 2001)
Business
Keywords: International business enterprises - Law; Commercial law; International law; Foreign trade regulation; International marketing law; Export sales contracts; Privatization; Advertising